2012
DOI: 10.1038/ki.2012.67
|View full text |Cite|
|
Sign up to set email alerts
|

New insights into urea and glucose handling by the kidney, and the urine concentrating mechanism

Abstract: The mechanism by which urine is concentrated in the mammalian kidney remains incompletely understood. Urea is the dominant urinary osmole in most mammals and may be concentrated a 100-fold above its plasma level in humans and even more in rodents. Several facilitated urea transporters have been cloned. The phenotypes of mice with deletion of the transporters expressed in the kidney have challenged two previously well-accepted paradigms regarding urea and sodium handling in the renal medulla but have provided n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 206 publications
(276 reference statements)
1
63
0
2
Order By: Relevance
“…Again, however, cytochemical studies localized UT-A to urothelial cell cytoplasm and some cell membranes but apparently not the luminal cell apical membrane. Finally, we cannot rule out an as yet unidentified active urea transporter(s) playing a role in net transurothelial urea transport as hypothesized by Yang and Bankir (6,47). Interestingly, those authors suggested that the function of such a transporter would likely be to maintain the large urine-to-blood urea gradient by transporting urea from the umbrella cell against its gradient into luminal urine, rather than the converse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, however, cytochemical studies localized UT-A to urothelial cell cytoplasm and some cell membranes but apparently not the luminal cell apical membrane. Finally, we cannot rule out an as yet unidentified active urea transporter(s) playing a role in net transurothelial urea transport as hypothesized by Yang and Bankir (6,47). Interestingly, those authors suggested that the function of such a transporter would likely be to maintain the large urine-to-blood urea gradient by transporting urea from the umbrella cell against its gradient into luminal urine, rather than the converse.…”
Section: Discussionmentioning
confidence: 99%
“…To study the effects of dietary protein on net urothelial transport of urea, creatinine, and water, we used an in vivo rat bladder model designed to mimic physiological conditions. We placed groups of rats on 3-wk diets differing only by protein content (40,18,6, and 2%) and instilled 0.3 ml of collected urine in the isolated bladder of anesthetized rats. After 1 h dwell, retrieved urine volumes were unchanged, but mean urea nitrogen (UN) and creatinine concentrations fell 17 and 4%, respectively, indicating transurothelial urea and creatinine reabsorption.…”
mentioning
confidence: 99%
“…The tubular nephron can generate lactate from aerobic glycolysis, particularly in the pars recta, and use lactate for gluconeogenesis (20). The net contribution of this intrarenal Cori cycle to the lactate eventually excreted into the urine versus the fraction of filtered lactate that escapes reabsorption at the luminal side is undetermined in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been applied to investigate the morphology of the VB, which include studies on sections of silicone rubberinjected specimens (4,7), microdissection (28), and the pioneering histotopographic studies of Kriz et al from the 1960s to 1980s (19,(21)(22)(23). At present, there are still some discrepancies in the description of the architecture of the VB due to its complexity: the almost identical appearance of the tubules and vessels as well as their small caliber in the VB (6,24). It is important to know how these tubules and vessels are spatially arranged in the VB and the associated region, as the interstitial tissue here is sparse (13,18) [in contrast to the inner medulla (15,32)].…”
mentioning
confidence: 99%